Implementation of School Information System at Yaabunaya Fathul Khair Makassar Foundation - Kamaruddin; Nur Mustika; Emasari; Askar Taliang; Wisda; Erwin Gatot Amiruddin (Ceddi Journal of Education, 2022)
This research aims to determine the implementation of the school information system at the Yaabunaya Fathul Khair Foundation in Makassar and its impact on the school management process. The school information system is expected to facilitate interaction between the school and various parties and produce accurate information. The analysis method used is the PIECES method which uses six variables, namely Performance, Information, Economics, Control, Efficiency, and Service, to identify and solve problems at the foundation. The research design uses UML, coding uses PHP, and the database uses MySQL. The system testing was done using the Black Box method to determine whether the system runs functionally or not. The result showed that the developed system can run well according to its function. The user's response to the built information system, based on the results of a questionnaire from 6 respondents with 10 questions, showed an average value of 86.79%, which means that the application functions well and is in line with expectations.